PENINGKATAN KOMPETENSI STRUKTUR DAN KOSAKATA BAHASA JERMAN SISWA MELALUI IMPLEMENTASI KONSEP ROLLENKARTEN - Lestuny, Carolina; Wenno, Eldaa Crystle; Noya van Delzen, June Carmen (German für Gesellschaft (J-Gefüge), 2025)
This community service activity aims to improve students’ competence in German grammar and vocabulary at the A2.2 level through the implementation of Rollenkarten (role cards). This learning method is designed to create a more interactive, contextual, and engaging learning environment, enabling students to apply grammar and vocabulary functionally in real-life situations. The activity applied a descriptive qualitative approach involving planning, implementation, data collection, and analysis. Data were collected through observation, documentation, and questionnaires administered before and after the learning sessions. The results show that the use of Rollenkarten increased students’ interest, motivation, and active participation. Furthermore, the method encouraged collaboration, improved students' confidence in speaking, and enhanced their understanding of the material. In conclusion, Rollenkarten is an effective learning strategy for improving students’ German grammar and vocabulary skills, although its success depends on careful planning and the teacher’s ability to manage the classroom effectively.